Fauna and flora of the brazilian Atlantic Forest: Educational theories and practices in favor of environmental preservation - Gibbs, Jucilene da Costa; Donato, Valéria Aparecida Di (Seven Editora, 2024)
This article discusses a study proposal, elaborated through concrete activities, in direct contact with nature, about a contribution to the resolution of specific situations of environmental damage, in the spaces close to the educational center, to reinforce the role of practice in the formation of values and in the development of proactive attitudes concerning the problems in question. whose vision lies in the urgency to act collectively in sensitizing and raising awareness about the importance of preserving the environment (fauna and flora), which has a remarkable relevance in the Brazilian Atlantic Forest. The didactics presented integrates the study of the characteristics, conditions, and benefits of an ecological reserve in the Atlantic Forest of the Southeast region, where the purposes are analyzed according to the level of education of the participants, emphasizing the formation of children and adolescents. At this stage of life, the primacy for the construction of environmental values corresponds to several pedagogical concepts, because as learning at this early stage is produced in greater depth, children learn more through motivations and obtain better practical skills. DOI:https://doi.org/10.56238/sevened2023.001-002